Extracellular Vesicles From Prostate Cancer‐Corrupted Osteoclasts Drive a Chain Reaction of Inflammatory Osteolysis and Tumour Progression at the Bone Metastatic Site - Takaaki Tamura; Tomofumi Yamamoto; Akiko Kogure; Yusuke Yoshioka; Yusuke Yamamoto; Shinichi Sakamoto; Tomohiko Ichikawa; Takahiro Ochiya (Journal of Extracellular Vesicles)
ABSTRACT Advanced‐stage prostate cancer (PCa) frequently causes bone metastases, resulting in a poor prognosis and a 5‐year survival rate of 30%. PCa bone metastasis is a highly complex and fluctuating process, comprising of osteolytic (bone‐degrading) and osteogenic (bone‐forming) lesions. Although this system is mainly controlled by alterations in the receptor activator of NF‐κB ligand (RANKL), RANKL‐based treatment does not prolong the overall survival of patients with PCa bone metastasis. Therefore, it is essential to understand the other interactions between tumour cells and bone‐resident cells in the metastatic niche to develop novel treatments. Extracellular vesicles (EVs) play key roles in intercellular communication and actively function in the bone microenvironment. We report that PCa cells corrupt osteoclasts (OCs) via their secretomes, inducing a pathological phenotype. EVs from pathological OCs activate bone‐resorbing OCs and suppress bone‐forming osteoblasts (OBs), leading to bone destruction. Pathological OCs increased IL‐1β secretion and produced EVs with miR‐5112 and miR‐1963, targeting Parp1 in OCs and Hoxa1 in OBs. This led to OC maturation and IL‐1β secretion, and inhibited OB mineralization. Injection of these miRNAs in vivo promoted PCa metastasis‐disrupting bone. We report the mediation of EVs from OCs under pathological conditions that modulate the bone metastatic niche independently of RANKL.